Battle royale [videorecording (DVD)] = tokubetsu-hen - Takami, Kōshun (Anchor Bay Entertainment, 2012)
In the future, the Japanese government captures a class of ninth-grade students and forces them to kill each other under the revolutionary 'Battle Royale' act. 42 Students, Three Days, One Survivor, No Rules. Bonus features included.